EVALUASI PELATIHAN VOKASI KEMENTERIAN KETENAGAKERJAAN SELAMA PERIODE PANDEMI COVID-19 (2021) - Stevanus Agung Wibowo; Sinta Ningrum; Tomi Setiawan (JANE - Jurnal Administrasi Negara, 2023)
A study based on the Covid-19 pandemic situation and government policies to reduce unemployment through vocational training. But his Department of Labor job training program during the COVID-19 pandemic in 2021 didn't make much of an impact. This study aims to determine the evaluation of the Department of Labor's vocational training programs during his COVID-19 pandemic in 2021. This survey was conducted using a qualitative approach using the CIPP counseling theory. Data collection methods used unstructured and/or semistructured observations and interviews, documents, and literature review. The study used data analysis techniques with three stages, in the form of data condensation, data presentation, and conclusion drawing and verification. The results of the study concluded that the vocational training program at the Ministry of Manpower had not been successful in terms of input, process, and product aspects. From the input aspect, vocational training resources are not sufficient. From the aspect of the process, there are still obstacles in the realization of training, supervision, and instructor skills. Meanwhile, from the product aspect, it is not possible to ensure that participants are placed after being trained.  Penelitian berdasarkan kondisi pandemi covid-19, dan kebijakan pemerintah dalam mengurangi angka pengangguran dengan pelatihan vokasi. Akan tetapi program pelatihan vokasi di Kementerian Ketenagakerjaan selama periode pandemi covid-19 pada tahun 2021 tidak memberikan dampak yang signifikan. Penelitian ini bertujuan untuk mengetahui evaluasi program pelatihan vokasi kementerian ketenagakerjaan selama periode pandemi covid-19 pada tahun 2021. Penelitian dilakukan melalui pendekatan kualitatif, menggunakan guidance theory CIPP. Metode pengumpulan data menggunakan  observasi dan wawancara tidak terstruktur dan/atau semi terstruktur, dokumen, dan studi literatur. Penelitian memakai teknik analisis data dengan tiga tahapan, berupa kondensasi data, penyajian data, serta penarikan kesimpulan dan verifikasi. Hasil penelitian menyimpulkan program pelatihan vokasi yang berada di Kementerian Ketenagakerjaan  belum berhasil dilihat dari aspek input, proses, dan produk. Dari aspek input, sumber daya pelatihan vokasi belum mencukupi kebutuhan. Dari aspek proses, masih memiliki kendala pada realisasi pelatihan, pengawasan, dan  skills instruktur. Sedangkan dari aspek produk tidak bisa memastikan peserta ditempatkan setelah dilatih.